An enthnographic study of Sarawak malay ESL teacher trainees - Norsarihan Ahmad (2016)
This is a qualitative, ethnographic case study which explored the training endeavours of 4 Sarawak Malay teacher trainees in the TESL degree programme in an Institute of Teacher Education (ITE) in Sarawak. The purpose of ethnographic case study was to uncover the emic and etic perspectives of the Sarawak Malay ESL teacher trainees. Purposeful sampling was carried out as the participants were able to provide rich information. The data were collected through classroom observations, unstructured interviews and field notes in order to present authentic data as possible. The various data collection of the teacher trainees were meant for data triangulation through member checking, constant engagement with the setting and the audit trail techniques were used to ensure validity and reliability of the data. A three-step coding approach, which includes the open, axial and selective coding stages were used to organize the collection of data. The within-case-analysis was used to compare the data for overlap and redundancy while the cross-case analysis was carried out after the within-case analysis. The findings of this study revealed that the socializing agents in social relationship, cultural misfit, linguistic confusion, learning to teach and self-tunnelling develop the awareness of self-concept and cultural identity which presents foundation for the teacher trainees to define their beliefs in terms of other people’s perspectives. Thus, teacher trainers need to view these teacher trainees as cultural being by embracing the diversity and validate the cultural identity of the teacher trainees. Therefore, understanding the learners’ characteristics and integrating Culturally Responsive Teaching Approach focusing on the inculcation of positive teachers’ attitudes and behaviours of future teachers in ITE need to be established to model tolerance and appreciation of teacher trainees’ differences in the teacher training programme. Based on the findings, a proposed typology of Sarawak Malay ESL teacher trainees’ traits was posited in the hope that future trainers can better understand and ameliorate the challenges faced by the Sarawak Malay ESL teacher trainees in their endeavour as future ESL teachers in Sarawak.